1979
DOI: 10.1063/1.90959
|View full text |Cite
|
Sign up to set email alerts
|

CF4 plasma etching on LiNbO3

Abstract: Deep anisotropic LiNbO3 etching with SF6/Ar inductively coupled plasmas J. Vac. Sci. Technol. B 30, 011208 (2012); 10.1116/1.3674282 40-50MHz lithium niobate (LiNbO3) transducers for pulsed Doppler measurements in mouse embryos

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…RIE is in itself a highly controllable and versatile dry process involving both physical and chemical effects to achieve directive and anisotropic material removal. It has already been demonstrated that lithium niobate can be dry etched using fluorine-based chemistries, [14][15][16][17] and ICP-RIE has previously been used on X-or Z-axis crystallographic orientations of lithium niobate to successfully fabricate ridge waveguides or photonic crystals, usually after proton exchange [18][19][20] but there is no report of any specific process allowing to dry etch structures that are several microns in depth in lithium niobate. The fabrication of very deep or very high aspect ratio structures is actually seriously impaired by the formation of lithium fluoride ͑LiF͒ compounds during the etching process that are relatively nonvolatile, leading to redeposition phenomena impeding the material removal.…”
Section: Introductionmentioning
confidence: 98%
“…RIE is in itself a highly controllable and versatile dry process involving both physical and chemical effects to achieve directive and anisotropic material removal. It has already been demonstrated that lithium niobate can be dry etched using fluorine-based chemistries, [14][15][16][17] and ICP-RIE has previously been used on X-or Z-axis crystallographic orientations of lithium niobate to successfully fabricate ridge waveguides or photonic crystals, usually after proton exchange [18][19][20] but there is no report of any specific process allowing to dry etch structures that are several microns in depth in lithium niobate. The fabrication of very deep or very high aspect ratio structures is actually seriously impaired by the formation of lithium fluoride ͑LiF͒ compounds during the etching process that are relatively nonvolatile, leading to redeposition phenomena impeding the material removal.…”
Section: Introductionmentioning
confidence: 98%
“…RIE is in itself a highly controllable and versatile dry process involving both physical and chemical effects to achieve directive and anisotropic material removal. It has already been demonstrated that LiNb0 3 can be dry etched using fluorin-based chemistries [6]- [12] although most of the reported works are dedicated to optical cuts (namely X-and Z-cuts). There is however no report of any specific process allowing to dry etch structures that are several microns in depth in lithium niobate.…”
Section: Introductionmentioning
confidence: 99%
“…Similar ideas have been developed by many authors in terms of fuzzy DM, BEC DM, wave DM or ultra-light axions [8,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36]. These models of dark mater (Scalar field dark matter: SFDM hereafter) have been shown to be able to explain the observed rotation curves [22,[37][38][39][40][41], the large scale structures of the universe [9], the minimum mass and the size of galaxies [42,43], the cosmic background radiation, spiral arms [44] and more. Works have also been done on the stability of BEC halos [45].…”
Section: Introductionmentioning
confidence: 99%